The Pragmatic Functions of (Now) in Informal Arabic in Saudi Arabia - Almohawes, Monera (International Journal of Linguistics, 2023)
The present study aims to investigate the pragmatic meaning and functions of halhen (now) as a discourse marker in informal Arabic. To do so, the researcher implemented Aijmer’s (2002) classification of the discourse functions of now. The results show that halhen has textual and affective functions. Regarding its textual functions, halhen could be a topic changer for telling new information or returning to an earlier point; a frame between discourse units; a turn-taking signal; an item separating sub-topics; a marker of a new step in an argument; a marker of a new action in a cumulative series of actions; or an indicator of background information in the form of elaboration, explanation, clarification, or support. The findings also indicate that halhen, in its affective functions, works as a marker of affective stance for evaluation, an expression introducing the speaker’s opinion in contrast to others, a shift in the perspective, or as a hearer-oriented intensifier.